2016
DOI: 10.1371/journal.pone.0151250
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Bacteriochlorophyll a and the Early Diversification of Photosynthesis

Abstract: Photosynthesis originated in the domain Bacteria billions of years ago; however, the identity of the last common ancestor to all phototrophic bacteria remains undetermined and speculative. Here I present the evolution of BchF or 3-vinyl-bacteriochlorophyll hydratase, an enzyme exclusively found in bacteria capable of synthetizing bacteriochlorophyll a. I show that BchF exists in two forms originating from an early divergence, one found in the phylum Chlorobi, including its paralogue BchV, and a second form tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…This pattern is also observed in Fig. 1 which also contained non-phototrophic representatives of the same phyla and it is consistent with previous phylogenetic (Quaiser et al 2003, Bryant et al 2012, Sousa et al 2013, Greening et al 2015, Cardona 2016a) and phylogenomic (Ciccarelli 2006, Dutilh et al 2008, Wu and Eisen 2008, Ward et al 2009, Jun et al 2010, David and Alm 2011, Rinke et al 2013, Segata et al 2013, Marin et al 2017) studies that have repeatedly confirmed the Acidobacteria as a sister clade of the Proteobacteria, or branching within the Proteobacteria as a sister clade of the deltaproteobacteria. At the same time, the nearness of the Chlorobi to Acidobacteria and Proteobacteira is also consistent with the ChlorobiBacteroidetes-Fibrobacterere supergroup bifurcating prior to the radiation of the Proteobacteria (Wu and Eisen 2008, Jun et al 2010, David and Alm 2011, Segata et al 2013, Marin et al 2017.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This pattern is also observed in Fig. 1 which also contained non-phototrophic representatives of the same phyla and it is consistent with previous phylogenetic (Quaiser et al 2003, Bryant et al 2012, Sousa et al 2013, Greening et al 2015, Cardona 2016a) and phylogenomic (Ciccarelli 2006, Dutilh et al 2008, Wu and Eisen 2008, Ward et al 2009, Jun et al 2010, David and Alm 2011, Rinke et al 2013, Segata et al 2013, Marin et al 2017) studies that have repeatedly confirmed the Acidobacteria as a sister clade of the Proteobacteria, or branching within the Proteobacteria as a sister clade of the deltaproteobacteria. At the same time, the nearness of the Chlorobi to Acidobacteria and Proteobacteira is also consistent with the ChlorobiBacteroidetes-Fibrobacterere supergroup bifurcating prior to the radiation of the Proteobacteria (Wu and Eisen 2008, Jun et al 2010, David and Alm 2011, Segata et al 2013, Marin et al 2017.…”
Section: Resultssupporting
confidence: 91%
“…From this perspective, our results suggest that the last common ancestor of Bacteroidetes and Chlorobi was phototrophic and that the phylum Bacteroidetes and other nonphototrophic Chlorobi evolved after losses of photosynthesis, as a mechanism of adaptation to heterotrophic or symbiotic lifestyles. Furthermore, the phylogeny of FtsH confirms the phylogenetic proximity of Acidobacteria and Proteobacteria, which is also replicated in evolutionary studies of the bacteriochlorophyll synthesis pathway (Sousa et al 2013, Cardona 2016a, showing unequivocally that the last common ancestor of Acidobacteria and Proteobacteria was also capable of phototrophy (Cardona 2015). This implies that deltaproteobacteria and non-phototrophic gamma-, beta-, and alpha-proteobacteria diversified after losses of photochemical RCs.…”
Section: Discussionsupporting
confidence: 63%
“…PCC 6803; the membranes were solubilized using 2% dodecyl-β-maltoside and loaded on 4%–14% clear-native gel (41). Abbreviations used: PSI[ 1 ] and PSI[ 3 ], monomer and trimer of PSI, respectively; PSII[ 2 ], dimer of PSII; CpcA/B[ 6 ], approximately 100 kDa heterohexamer of CpcA and CpcB phycobilinoproteins. (B) Colored bands corresponding to PS complexes of G .…”
Section: Supporting Informationmentioning
confidence: 99%
“…Photosynthetic (PS) microorganisms play an important role in many of Earth’s ecosystems due to their ability to harvest light and convert it to metabolic energy [ 1 ]. So far, phototrophic species were found in 7 bacterial phyla: Cyanobacteria, Proteobacteria, Chlorobi, Chloroflexi, Firmicutes, Acidobacteria, and Gemmatimonadetes [ 2 ]. The conversion of light into metabolic energy occurs in reaction centers (RCs) that carry out charge separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation